Scope of application of some medicinal plants in the Kazakh-Turkish language and cultur (Journal of Oriental Studies, 2019)
While the biological structures and properties of plants in the Kazakh steppe have been studied by Russian specialists since the last century, it can be said that the national, linguistic, historical, literary studies of the names of the Kazakh people for plants and herbs have decreased. Onomastics, toponymy of each country, demonstrates beliefs, dreams, joy and grief, suffering and grief, and passes them on to the next generation, other people. Plants play an important role in people’s lives; therefore, in many countries, plant names are not given by word of mouth, but on one occasion, an event, the medicinal properties of plants, natural phenomena, or a human soul. This may be due to legends about the names of plants. In our article we will try to analyze the use of plant names in the Kazakh and Turkish languages and culture, including the use of plants with healing properties, human legends, as well as similar and not similar features. Key words: plant names, medicinal plants, KazakhTurkish culture.